A permanent magnetic material Nd2Fe 14 B single-phase compound and its preparation method and application
The Fe-B alloy and the Nd source ingot are closely combined through plastic deformation by vacuum heat pressing under high temperature and high pressure, solving the problem of difficulty in preparing Nd2Fe14B single-phase compounds in the prior art, and achieving experimental determination of their diffusion and growth behavior.
Patent Information
- Application Number
- CN202510091778.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The prior art is difficult to obtain Nd2Fe14B single-phase compound through smelting methods, and the traditional diffusion couple preparation method cannot effectively bind Nd and B elements, resulting in the inability to study their diffusion and growth behavior.
The vacuum heat pressing method was used to achieve close bonding of the interface through plastic deformation under high temperature and high pressure, and the Nd2Fe14B single-phase compound was prepared.
The difficulties in diffusion and growth of Nd2Fe14B compounds were successfully solved, and the preparation of Nd2Fe14B single-phase compounds and experimental determination of diffusion and growth behavior were realized.
Smart Images

Figure CN119517603B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a single-phase Nd2Fe 14 B permanent magnetic material and its preparation method and application belong to the technical field of permanent magnetic material preparation. Background Art
[0002] Nd-Fe-B permanent magnet materials are widely used in electronics, aerospace, and wind turbine driving industries due to their excellent properties, such as high remanence, high coercivity, and high magnetic energy product. 14 B is the main phase of Nd-Fe-B permanent magnet material and the main reason for its excellent magnetic properties. Understanding its size, shape and distribution plays a decisive role in regulating the performance of permanent magnet materials. 14 The diffusion growth behavior of B compounds is crucial to further control and improve material properties. 14 B is a stoichiometric compound. If it is smelted, even if the measurement is accurate, there will be deviations, and during the smelting process, there will be volatilization of elements, so Nd2Fe cannot be obtained by smelting. 14 In addition, because Nd is very easy to oxidize, and Nd and B have high hardness and poor plasticity, the traditional diffusion couple preparation method cannot effectively combine the diffusion couple interface and cannot obtain Nd2Fe 14 B single-phase compound, so Nd2Fe cannot be obtained 14 Diffusion growth behavior of B. Summary of the invention
[0003] Based on the shortcomings of the prior art, the first object of the present invention is to provide a permanent magnetic material Nd2Fe 14 The preparation method of the present invention uses vacuum hot pressing to avoid the problem of interface oxidation while allowing the diffusion components to undergo plastic deformation under high temperature and high pressure to achieve close bonding of the diffusion couple interface, thereby obtaining the permanent magnetic material Nd2Fe 14 B single-phase compound, Nd2Fe 14 Experimental determination of the diffusion growth behavior of B compounds.
[0004] The second object of the present invention is to provide a permanent magnetic material Nd2Fe prepared by the above preparation method. 14 B single-phase compound.
[0005] The third object of the present invention is to provide a permanent magnetic material Nd2Fe prepared by the above preparation method. 14 B Application of single-phase compounds.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The present invention discloses a permanent magnetic material Nd2Fe 14 The preparation method of the B single-phase compound comprises the following steps: homogenizing and annealing the Fe-B alloy ingot and the Nd source ingot to obtain the Fe-B alloy annealing billet and the Nd source annealing billet respectively, placing the Fe-B alloy annealing billet and the Nd source annealing billet in contact with each other in a hot pressing mold, and then performing solid phase diffusion under vacuum hot pressing to obtain a diffusion couple, and annealing the diffusion couple to obtain the compound;
[0008] In the Fe-B alloy ingot, the atomic fraction of B is 5-25 at.%;
[0009] The Nd source ingot is selected from a pure Nd ingot or a Nd-Fe alloy ingot;
[0010] In the Nd-Fe alloy ingot, the atomic fraction of Fe is ≤60 at.%;
[0011] The temperature of the vacuum hot pressing is 600-680° C., the pressure is 400-500 MPa, the heat preservation time is 50-60 min, and the pressure preservation time is 5-10 min.
[0012] The present invention adopts Fe-B alloy and Nd source as raw materials, and after homogenization annealing, places the annealed blanks in contact with each other in a hot pressing mold, and plastically deforms the annealed blanks by vacuum hot pressing. Each annealed blank undergoes solid phase diffusion through plastic deformation to achieve good interface bonding and form Nd2Fe 14 B single-phase compound, and finally annealing and further diffusion to obtain Nd2Fe with a certain thickness 14 B single-phase compound.
[0013] In the present invention, firstly, Nd2Fe 14 B single-phase compound, on the one hand, Fe-B alloy needs to be used, and the atomic fraction of B in the Fe-B alloy needs to be controlled to 5-25at.%, on the other hand, solid phase diffusion needs to be controlled during vacuum hot pressing, otherwise Nd2Fe 14 B single-phase compound.
[0014] In the present invention, the parameters of vacuum hot pressing need to be effectively controlled, not only to achieve plastic deformation, but also to control solid phase diffusion, otherwise Nd2Fe 14 For single-phase compounds B, if the temperature of vacuum hot pressing is too high, a liquid phase will appear, which will not only affect the bonding, but more importantly, will form a mixed phase. If the temperature is too low, the conditions for plastic deformation cannot be met, and the interface is difficult to bond. If the pressure is too small, the plastic deformation conditions of the alloy cannot be met, making it difficult to bond the interface. If the pressure is too high, it will not only cause deformation of the mold and damage to the diffusion couple, but also may cause the generation of mixed phases.
[0015] A preferred solution is to perform homogenization annealing on two Fe-B alloy ingots with different B contents and one Nd source ingot to obtain Fe-B alloy annealing billets and Nd source annealing billets, respectively, and then place them together in a hot pressing mold in a contact manner with the Nd source annealing billet in the middle and the two Fe-B alloy annealing billets with different B contents placed on both sides; or to perform homogenization annealing on one Fe-B alloy annealing billet and two Nd source annealing billets with different Nd contents to obtain Fe-B alloy annealing billets and Nd source annealing billets, respectively, and then place them together in a hot pressing mold in a contact manner with the Fe-B alloy annealing billet in the middle and the two Nd source annealing billets with different Nd contents placed on both sides.
[0016] In the present invention, three components are used to carry out Nd2Fe 14 The preparation of B single-phase compounds can not only better combine under hot pressing, but also be better used to understand the diffusion growth behavior of alloy components with different compositions.
[0017] In a preferred embodiment, in the Fe-B alloy ingot, the atomic fraction of B is 5-20 at.%.
[0018] In a preferred embodiment, in the Nd-Fe alloy ingot, the atomic fraction of Fe is 25-55 at.%.
[0019] In a preferred embodiment, the Fe-B alloy ingot is obtained by mixing pure iron and Fe-B master alloy according to a designed ratio and then smelting the alloy repeatedly. In the Fe-B master alloy, the atomic fraction of B is 45-60 at.%.
[0020] In a preferred solution, the Nd-Fe alloy ingot is obtained by mixing pure Nd and pure Fe in a designed ratio and then smelting them repeatedly.
[0021] In a preferred embodiment, the homogenization annealing temperature is 600-680°C and the homogenization annealing time is 7-10 days. The homogenization annealing at the above temperature and time can make the annealed blank fully homogenized while avoiding excessive volatilization of rare earth.
[0022] In the actual operation process, the Fe-B alloy ingot and the Nd source ingot are cut according to the end face shape and size of the upper and lower dies in the vacuum hot pressing mold, and then homogenized annealing is performed. Then, the three annealed billets obtained by homogenization annealing are polished with 400, 800, 1500, and 2000 mesh sandpapers in turn, polished with 0.25 μm diamond polishing paste on a polishing cloth, and then placed in alcohol for ultrasonic treatment for more than 15 minutes.
[0023] Preferably, the hot pressing mold includes a female mold, a receiving groove of the female mold, a lower mold fixed to the bottom of the receiving groove, an upper mold embedded in the receiving groove and slidable along the axis, a cover plate sleeve covering the upper mold and fitting during work, and a stripping module.
[0024] In a preferred solution, the hot pressing mold is made of H13 steel. Using the mold made of the above material can ensure that the mold does not deform during hot pressing, thereby ensuring the effect of generating diffusion couples.
[0025] In the actual operation process, the obtained diffusion couple was polished with 400, 800, 1500, and 2000 grit sandpaper, and then polished with 0.25 μm diamond polishing paste on a polishing cloth, placed in alcohol for ultrasonic treatment for more than 15 minutes, and dried in a vacuum drying oven before using EPMA to observe the microstructure.
[0026] In a preferred embodiment, the annealing temperature is 500-680° C. and the annealing time is 5-28 days.
[0027] In the present invention, an annealing temperature that is too high or too low will seriously affect the experimental results. A temperature that is too low will lead to too slow diffusion, while a temperature that is too high will lead to the generation of a liquid phase, both of which are not conducive to the diffusion growth of the compound.
[0028] Nd2Fe with different thickness can be obtained by using different annealing times at the same annealing temperature. 14 B intermetallic compound layer.
[0029] The present invention also provides a permanent magnetic material Nd2Fe prepared by the above preparation method 14 B single-phase compound.
[0030] The present invention also provides a permanent magnetic material Nd2Fe prepared by the above preparation method 14 B single-phase compound application, the permanent magnet material Nd2Fe 14 B single-phase compound is used to observe the acquisition of Nd2Fe 14 The growth behavior of B.
[0031] Beneficial effects of the present invention:
[0032] The present invention provides a permanent magnetic material Nd2Fe 14 The preparation method of single-phase compound B successfully solved the experimental study of Nd2Fe 14The present invention adopts the method of homogenizing annealing the Fe-B alloy ingot and the Nd source ingot to obtain the Fe-B alloy annealing billet and the Nd source annealing billet respectively, placing the Fe-B alloy annealing billet and the Nd source annealing billet in contact with each other in a hot pressing mold, and then plastically deforming the three annealing billets under vacuum hot pressing. Each annealing billet undergoes solid phase diffusion through plastic deformation to achieve good interface bonding, obtain a diffusion couple, and finally annealing to diffuse and obtain Nd2Fe 14 B single-phase compound.
[0033] The preparation method provided by the present invention successfully solves the problem of studying Nd2Fe 14 The difficulty of diffusion growth of B compound is of great significance for studying the diffusion growth of compounds containing easily oxidizable elements, high hardness and poor plasticity, and the problem that it is difficult to prepare samples by traditional methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings and attached tables required for describing the embodiments. Obviously, the drawings and attached tables in the following description only represent some implementations of the present invention. For those of ordinary skill in the art, other relevant drawings and attached tables can also be obtained based on these drawings and attached tables.
[0035] Figure 1 Schematic diagram of the structure of the vacuum hot pressing mold in the embodiment, in which (1) is the female mold, (2) is the receiving groove, (3) is the upper mold, (4) is the lower mold, (5) is the stripping module, and (6) is the cover plate sleeve.
[0036] Figure 2 The sample prepared in Example 1 was annealed at 650 °C for 5 days and the composition of positions "7", "8" and "9" was measured by EPMA. The results are shown in Table 1. From the composition of EPMA, it can be judged that the new phase is Nd2Fe 14 B. Judging from the composition of EPMA, the new phase is Nd2Fe 14 B, in the figure, 7, 8, and 9 are marking points at different positions within the diffusion interface.
[0037] Figure 3 The BSE microscopic images of the sample prepared in Example 1 after annealing at 650°C for 5, 10, 15 and 20 days, wherein: Figure 3 (a) is a BSE microscopic image of the sample prepared in Example 1 annealed at 650 °C for 5 days. Figure 3 (b) is a BSE microscopic image of the sample prepared in Example 1 annealed at 650 °C for 10 days. Figure 3 (c) is a BSE microscopic image of the sample prepared in Example 1 annealed at 650 °C for 15 days. Figure 3(d) is a BSE microscopic image of the sample prepared in Example 1 annealed at 650 °C for 20 days.
[0038] Figure 4 The sample prepared in Example 2 was annealed at 600 °C for 7 days and the composition of the positions "10", "11" and "12" was measured by EPMA. The results are shown in Table 2. From the composition of EPMA, it can be judged that the new phase is Nd2Fe 14 B, in the figure, 10, 11, and 12 are marking points at different positions within the diffusion interface.
[0039] Figure 5 The BSE microscopic images of the sample prepared in Example 2 after annealing at 600°C for 7, 14, 21 and 28 days, wherein: Figure 5 (a) is a BSE microscopic image of the sample prepared in Example 2 after annealing at 600 °C for 7 days. Figure 5 (b) is a BSE microscopic image of the sample prepared in Example 2 after annealing at 600 °C for 14 days. Figure 5 (c) is a BSE microscopic image of the sample prepared in Example 2 after annealing at 600 °C for 21 days. Figure 5 (d) is a BSE microscopic image of the sample prepared in Example 2 annealed at 600 °C for 28 days.
[0040] Figure 6 The sample prepared in Example 3 was annealed at 550 °C for 7 days and the composition of the positions "13", "14" and "15" was measured by EPMA. The results are shown in Table 3. From the composition of EPMA, it can be judged that the new phase is Nd2Fe 14 B, in the figure, 13, 14, and 15 are marking points at different positions within the diffusion interface.
[0041] Figure 7 This is a BSE microscopic image of the sample prepared in Example 3 after annealing at 550°C for 7 days. DETAILED DESCRIPTION
[0042] Example 1
[0043] Nd 45 Fe 55 -Fe 90 B 10 -Nd 70 Fe 30 Preparation of diffusion couple
[0044] (1) Preparation of alloy raw materials
[0045] 99.5wt.% Nd and 99.99wt.% Fe were used as raw materials and melted in a high vacuum arc melting furnace for more than 5 times to obtain 45 at.% Nd-55 at.% Fe alloy ingots and 70 at.% Nd-30 at.% Fe alloy ingots. 99.99wt.% Fe and 83.76wt.% Fe-16.22 wt.% B alloy were used as raw materials and melted in a high vacuum arc melting furnace for more than 5 times to obtain 90 at.% Fe-10 at.% B alloy ingots. 45 at.% Nd-55 at.% Fe alloy ingot, 70 at.% Nd-30 at.% Fe alloy ingot, 90 at.% Fe-10 at.% B alloy ingot were cut into discs with diameter = 10 mm and thickness = 3 mm, homogenized and annealed at 650 °C for 7 days, and then the three annealed blanks were polished with 400, 800, 1500, and 2000 mesh sandpapers, and then polished with 0.25 μm diamond polishing paste on a polishing cloth, and ultrasonically treated in alcohol for more than 15 minutes;
[0046] (2) Preparation of diffusion couple
[0047] The mold is made of H13 material, and its structural diagram is as follows Figure 1 As shown, it includes a female mold (1), a receiving groove (2), an upper mold (3) embedded in the receiving groove (2) and slidable along the axis of the receiving groove, a lower mold (4) fixed to the bottom of the receiving groove, a demolding module (5) and a cover plate sleeve (6). According to the order of 45 at.%Nd-55 at.%Fe annealing billet, 90 at.%Fe-10 at.%B annealing billet and 70 at.%Nd-30 at.%Fe annealing billet, the three prepared annealing billet discs are placed between the upper and lower molds and then placed on the pressing platform of a vacuum hot pressing furnace for vacuum hot pressing; and the vacuum hot pressing temperature is controlled to be 650°C, the pressure is 450Mpa, the holding time is 55min, and the holding time is 8min. After cooling, the mold is removed and demolded, and the diffusion couple sample is taken out;
[0048] The obtained diffusion couple was polished with 400, 800, 1500, and 2000 grit sandpapers, then polished with 0.25 μm diamond polishing paste on a polishing cloth, placed in alcohol for ultrasonic treatment for more than 15 minutes, and dried in a vacuum drying oven before using EPMA to observe the microstructure;
[0049] (3) Annealing
[0050] The diffusion couple samples were then packaged into a vacuum quartz tube and placed in a tube furnace for annealing at 650 °C for 5, 10, 15 and 20 days.
[0051] (4) Determination of compounds: The samples were analyzed by EPMA to form Nd2Fe14 B intermetallic compounds and detect composition distribution; Figure 2 The sample prepared in Example 1 was annealed at 650°C for 5 days and the composition of positions "7", "8", and "9" was measured by EPMA. The results are shown in Table 1. From the composition of EPMA, it can be judged that the new phase is Nd2Fe 14 B.
[0052]
[0053] (5) Growth thickness observation: Select different regions of the diffusion couple with the same annealing time to measure the Nd2Fe 14 The growth thickness of the B phase is taken as the annealing time Nd2Fe 14 The average growth of phase B, finally obtaining Nd2Fe 14 The relationship between the growth thickness of phase B and time, such as Figure 3 shown.
[0054] Example 2
[0055] Nd 75 Fe 25 -Fe 90 B 10 Preparation of Nd diffusion couple
[0056] (1) Preparation of alloy raw materials
[0057] 99.95wt.% Nd and 99.99wt.% Fe were used as raw materials and melted in a high vacuum arc melting furnace for more than 5 times to obtain 75 at.% Nd-25 at.% Fe alloy ingots and pure Nd ingots respectively. 99.99wt.% Fe and 83.76wt.% Fe-16.22wt.% B alloy were used as raw materials and melted in a high vacuum arc melting furnace for more than 5 times to obtain 90 at.% Fe-10 at.% B alloy ingots. 75 at.%Nd-25 at.%Fe, pure Nd ingot, 90 at.%Fe-10 at.%B alloy ingot were cut into discs with diameter = 10mm and thickness = 3mm, homogenized and annealed at 600℃ for 10 days, and then the three annealed blanks were polished with 400, 800, 1500, and 2000 mesh sandpapers, and then polished with 0.25 μm diamond polishing paste on a polishing cloth, and ultrasonically treated in alcohol for more than 15 minutes;
[0058] (2) Preparation of diffusion couple
[0059] The mold is made of H13 material, and its structural diagram is as follows Figure 1As shown, it includes a female mold (1), a receiving groove (2), an upper mold (3) embedded in the receiving groove (2) and capable of sliding along the axis of the receiving groove, a lower mold (4) fixed to the bottom of the receiving groove, a demolding module (5) and a cover plate sleeve (6). In the order of Nd-Fe alloy ingot annealing billet, Fe-B alloy ingot annealing billet and pure Nd ingot annealing billet, the three prepared annealing billet discs are placed between the upper and lower molds and then placed on the pressing platform of a vacuum hot pressing furnace for vacuum hot pressing; and the vacuum hot pressing temperature is controlled to be 600°C, the pressure is 400Mpa, the holding time is 50min, and the holding time is 5min. After cooling, the mold is removed and demolded, and the diffusion couple sample is taken out;
[0060] The obtained diffusion couple was polished with 400, 800, 1500, and 2000 grit sandpapers, then polished with 0.25 μm diamond polishing paste on a polishing cloth, placed in alcohol for ultrasonic treatment for more than 15 minutes, and dried in a vacuum drying oven before using EPMA to observe the microstructure;
[0061] (3) Annealing
[0062] The diffusion couple samples were then packaged into a vacuum quartz tube and placed in a tube furnace for annealing at 600 °C for 7, 14, 21, and 28 days.
[0063] (4) Determination of compounds: The samples were analyzed by EPMA to form Nd2Fe 14 B intermetallic compounds and detect composition distribution; Figure 4 The sample prepared in Example 2 was annealed at 600°C for 7 days and the composition of the "10", "11", and "12" positions was measured by EPMA. The results are shown in Table 2. From the composition of EPMA, it can be judged that the new phase is Nd2Fe 14 B.
[0064]
[0065] (5) Growth thickness observation: Select different regions of the diffusion couple with the same annealing time to measure the Nd2Fe 14 The growth thickness of the B phase is taken as the annealing time Nd2Fe 14 The average growth of phase B, finally obtaining Nd2Fe 14 The relationship between the growth thickness of phase B and time, such as Figure 5 .
[0066] Example 3
[0067] Fe 95 B5-Nd-Fe 80 B 20 Preparation of diffusion couple
[0068] (1) Preparation of alloy raw materials
[0069] 99.95wt.% Nd, 99.99wt.% Fe, 83.76wt.%Fe-16.22 wt.%B alloys were used as raw materials and melted in a high vacuum arc melting furnace for more than 5 times to obtain 95 at.%Fe-5 at.%B alloy ingots, 80 at.%Fe-20 at.%B alloy ingots and pure Nd ingots respectively. The 95 at.%Fe-5 at.%B alloy ingots, 80 at.%Fe-20 at.%B alloy ingots and pure Nd ingots were cut into discs with a diameter of 10 mm and a thickness of 3 mm, and homogenized and annealed at 680 °C for 10 days. Then, the three annealed blanks were polished with 400, 800, 1500, and 2000 mesh sandpapers, and then polished with 0.25 μm diamond polishing paste on a polishing cloth, and ultrasonically treated in alcohol for more than 15 minutes;
[0070] (2) Preparation of diffusion couple
[0071] The mold is made of H13 material, and its structural diagram is as follows Figure 1 As shown, it includes a female mold (1), a receiving groove (2), an upper mold (3) embedded in the receiving groove (2) and capable of sliding along the axis of the receiving groove, a lower mold (4) fixed to the bottom of the receiving groove, a demolding module (5) and a cover plate sleeve (6). In the order of 95 at.%Fe-5 at.%B alloy ingot annealing billet, pure Nd ingot annealing billet, and 80 at.%Fe-20 at.%B alloy ingot annealing billet, the three prepared annealing billet discs are placed between the upper and lower molds and then placed on the pressing platform of a vacuum hot pressing furnace for vacuum hot pressing; and the vacuum hot pressing temperature is controlled to be 680°C, the pressure is 500Mpa, the holding time is 60min, and the holding time is 10min. After cooling, the mold is removed and demolded, and the diffusion couple sample is taken out;
[0072] The obtained diffusion couple was polished with 400, 800, 1500, and 2000 grit sandpapers, and then polished with 0.25 μm diamond polishing paste on a polishing cloth, placed in alcohol for ultrasonic treatment for more than 15 minutes, and dried in a vacuum drying oven before using EPMA to observe the microstructure.
[0073] (3) Annealing
[0074] The diffusion couple sample was then packaged into a vacuum quartz tube and placed in a tube furnace for annealing at 550 °C for 7 days.
[0075] (4) Determination of compounds: The samples were analyzed by EPMA to form Nd2Fe 14 B intermetallic compounds and detect composition distribution; Figure 6The sample prepared in Example 3 was annealed at 550 °C for 7 days, and the composition of the positions "13", "14", and "15" was measured by EPMA. The results are shown in Table 3. From the composition of EPMA, it can be judged that the new phase is Nd2Fe 14 B.
[0076]
[0077] (5) Growth thickness observation: Select different regions of the diffusion couple with the same annealing time to measure the Nd2Fe 14 The growth thickness of the B phase is taken as the annealing time Nd2Fe 14 The average growth rate of phase B is Figure 7 .
[0078] Comparative Example 1
[0079] The other conditions were the same as those in Example 1, except that the 45 at.% Nd-55 at.% Fe alloy ingot was replaced with a 30 at.% Nd-70 at.% Fe alloy ingot. As a result, no diffusion interface was formed between the 30 at.% Nd-70 at.% Fe alloy and the 90 at.% Fe-10 at.% B alloy, and the diffusion couple interface could not be effectively combined, so Nd2Fe 14 B single-phase compound.
[0080] Comparative Example 2
[0081] The other conditions were the same as those in Example 1, except that the 90 at.% Fe-10 at.% B alloy ingot was replaced with 70 at.% Fe-30 at.% B. As a result, no diffusion interface was formed, the diffusion couple interface could not be effectively combined, and Nd2Fe 14 B single-phase compound.
[0082] Comparative Example 3
[0083] The other conditions were the same as those in Example 1, except that the vacuum hot pressing temperature was 580°C. No diffusion couple could be obtained successfully, and Nd2Fe 14 B single-phase compound.
[0084] Comparative Example 4
[0085] The other conditions were the same as those in Example 1, except that the vacuum hot pressing temperature was 700°C. During the hot pressing process, a liquid phase appeared, and diffusion couples could not be successfully obtained. Nd2Fe 14 B single-phase compound.
[0086] Comparative Example 5
[0087] The other conditions were the same as those in Example 1, except that the vacuum hot pressing pressure was 350 MPa. No diffusion couple could be obtained successfully, and Nd2Fe 14 B single-phase compound.
Claims
1. A permanent magnetic material Nd2Fe 14 B. A method for preparing a single-phase compound, characterized in that: The Fe-B alloy ingot and the Nd source ingot are both subjected to homogenization annealing to obtain Fe-B alloy annealed billets and Nd source annealed billets respectively, the Fe-B alloy annealed billets and the Nd source annealed billets are placed in contact with each other in a hot pressing mold, solid phase diffusion is performed under vacuum hot pressing to obtain a diffusion couple, and then the diffusion couple is annealed to obtain the result; In the Fe-B alloy ingot, the atomic fraction of B is 5-25 at.%; The Nd source ingot is selected from a pure Nd ingot or a Nd-Fe alloy ingot; In the Nd-Fe alloy ingot, the atomic fraction of Fe is ≤60 at.%; The temperature of the vacuum hot pressing is 600-680° C., the pressure is 400-500 MPa, the heat preservation time is 50-60 min, and the pressure preservation time is 5-10 min.
2. A permanent magnetic material Nd2Fe according to claim 1 14 B. A method for preparing a single-phase compound, characterized in that: Two Fe-B alloy ingots with different B contents and one Nd source ingot are homogenized annealed to obtain Fe-B alloy annealed billets and Nd source annealed billets, respectively. Then, the billets are placed in a hot pressing mold in a contact manner with the Nd source annealed billet in the middle and the two Fe-B alloy annealed billets with different B contents placed on both sides. Alternatively, one Fe-B alloy annealed billet and two Nd source annealed billets with different Nd contents are homogenized annealed to obtain Fe-B alloy annealed billets and Nd source annealed billets, respectively. Then, the billets are placed in a hot pressing mold in a contact manner with the Fe-B alloy annealed billet in the middle and the two Nd source annealed billets with different Nd contents placed on both sides.
3. A permanent magnetic material Nd2Fe according to claim 1 or 2 14 B. A method for preparing a single-phase compound, characterized in that: In the Fe-B alloy, the atomic fraction of B is 5-20 at.%; In the Nd-Fe alloy, the atomic fraction of Fe is 25-55 at.%.
4. A permanent magnetic material Nd2Fe according to claim 1 or 2 14 B. A method for preparing a single-phase compound, characterized in that: The Fe-B alloy is obtained by mixing pure iron and Fe-B master alloy according to the designed ratio, and then smelting them repeatedly. In the Fe-B master alloy, the atomic fraction of B is 45-60 at.%; Nd-Fe alloy ingots are obtained by mixing pure Nd and pure Fe in a designed ratio and then smelting them repeatedly.
5. A permanent magnetic material Nd2Fe according to claim 1 or 2 14 B. A method for preparing a single-phase compound, characterized in that: The homogenization annealing temperature is 600-680° C., and the homogenization annealing time is 7-10 days.
6. A permanent magnetic material Nd2Fe according to claim 1 or 2 14 B. A method for preparing a single-phase compound, characterized in that: The hot pressing mold comprises a female mold, a receiving groove of the female mold, a lower mold fixed at the bottom of the receiving groove, an upper mold embedded in the receiving groove and slidable along the axis, a cover plate sleeve covering the upper mold and fitting during work, and a stripping module; The material of the hot pressing mold is H13 steel.
7. A permanent magnetic material Nd2Fe according to claim 1 or 2 14 B. A method for preparing a single-phase compound, characterized in that: The temperature for annealing the diffusion couple is 500-680° C., and the time for annealing the diffusion couple is 5-28 days.
8. A permanent magnetic material Nd2Fe prepared by the preparation method according to any one of claims 1 to 7 14 B single-phase compound.
9. A permanent magnetic material Nd2Fe prepared by the preparation method according to any one of claims 1 to 7 14 Application of single-phase compound B, characterized by: The permanent magnetic material Nd2Fe 14 B single-phase compound is used to observe the acquisition of Nd2Fe 14 The growth behavior of B.
Citation Information
Patent Citations
Method for reducing oxygen content of sintered neodymium-iron-boron permanent magnet
CN111554499A
Preparation method of high-flux solid diffusion couple
CN114964990A